Antioxidant and acetylcholine esterase inhibition activity of the extract from Centella asiatica obtained by Ultrasound pre-treatment followed by Microwave-assisted extraction method - Sivaneshwaran, G.; Mariappan, Valarpriya; Subban, Ravi (Journal of Phytology, 2023)
The extraction of compounds from Centella asiatica a member of the family Apiaceae by adopting Ultrasound assisted Extraction (UAE), Microwave assisted extraction (MAE) and Ultrasound pre-treatment followed by Microwave-assisted extraction were reported. The yield of the extract, phenol content, antioxidant activity and Acetylcholine esterase activity were found to be more in the extract obtained by Ultrasound pre-treatment followed by Microwave-assisted extraction method. The yield of the extract is more by 30.8% to the UAE and MAE methods. The phenol content is 1289 ± 0.57 μg GAE/mL which is 27% higher than the MAE method and 46% higher than the UAE method. HPLC analysis showed that the C. asiatica extract comprised of Madecassoside in major quantity followed by madecassic acid, asiatic acid and asiaticoside. In the antioxidant activity by DPPH assay and AChE inhibitory effect the IC50, value for C. asiatica extract obtained by UAE pre-treated and followed by MAE method is 38.24 μg mL−1 and 26.7±0.49 mg/mL respectively which are substantially higher than the other two methods. So, Ultrasound pre-treatment followed by Microwave-assisted extraction method is found to be a preferable method to get the desired compounds from C. asiatica.